1997
DOI: 10.1111/1523-1747.ep12337639
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Human Keratinocytes Express Tropoelastin

Abstract: We detected elastin mRNA in cultured normal human keratinocytes by RNase protection assay. The content of elastin mRNA was estimated at approximately one-twentieth of that of cultured skin fibroblasts. Tropoelastin polypeptide with a molecular weight of 68 kDa was detected in the preparation of culture medium of normal human keratinocytes by western blot assays using anti-tropoelastin antibody. Immunohistochemical studies also demonstrated positive staining in cultured normal human keratinocytes as well as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…We have reported that a collagenous protein and tropoelastin are secreted by keratinocytes [31, 32]; in addition, we have confirmed the presence of elastin in the epidermis, particularly in the granular layer [unpubl. data].…”
Section: Discussionsupporting
confidence: 58%
“…We have reported that a collagenous protein and tropoelastin are secreted by keratinocytes [31, 32]; in addition, we have confirmed the presence of elastin in the epidermis, particularly in the granular layer [unpubl. data].…”
Section: Discussionsupporting
confidence: 58%
“…No data however have been presented on the role of elastin as an epidermal cell constituent. The observation of elastin molecule, but not necessarily elastic fibers, within the epidermis of the SE and other reports in the skin (Haynes et al, 1997;Kajiya et al, 1997;Seo et al, 2001) lead to future studies where it will be interesting to determine whether or not elastin can be deposited in normal human epidermis. In this regard, it is interesting to note that elastin peptides have been reported to influence the keratinocyte migration and differentiation (Fujimoto et al, 2000a, b).…”
Section: Discussionmentioning
confidence: 87%
“…Another candidate substrate for LOX or LOXL between keratinocytes might be elastin. Different reports have described the expression of elastin and microfibril mRNAs in keratinocytes (Haynes et al, 1997;Kajiya et al, 1997). Interestingly, it has been reported that elastin mRNA expression is increased after UV exposure in the epidermal layers (Seo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Since elastin and Fib-1 have been shown to be expressed by cultured keratinocytes [12,13], our findings indicate that keratinocytes potentially produce the three major components of elastic fibers (elastin, Fib-1 and MAGP-1) which are thought to be necessary to form the elastic fiber network.…”
Section: Discussionmentioning
confidence: 66%
“…Recently both proteins have been shown to be expressed by keratinocytes [12,13]. We studied the expression of MAGP-1 in cultured human keratinocytes and the localization of MAGP-1-immunoreactive fibers in the upper dermis.…”
Section: Introductionmentioning
confidence: 99%